Tingkat Partisipasi Masyarakat Terhadap Upaya Mengatasi Permasalahan Sampah - Dian Febrianti; Rahmat Djamaluddin; TEUKU FARİZAL; Edi Mawardi (Jurnal Serambi Engineering, 2024)
Garbage is the remnants of the use of human activities that are no longer needed. Garbage is one of the things that can have a negative impact on development. Improvement through the participation of the community is the key to the success of efforts to build a city in order to create a clean and safe city from the adverse effects caused by waste. In 2019 the West Aceh District Environmental Service (DLHK) has carried out at least 129 m3 of garbage dumping and is only able to handle 114.3 m3 of waste from the total services spread across four sub-districts which are waste management services, namely Johan Pahlawan District of 66,601 m3, Samatiga 15,787 m3, Meureubo 31,486 m3, and Kaway XVI 22,524 m3. So waste becomes one of the serious problems for sustainable city development and a countermeasures must be taken. This research method uses the Likert scale method, the results of the calculation of the number of samples using the Slovin formula are 41 respondents. From the results of calculations based on the questionnaire submitted to the respondents, the score was 40.878%. So the conclusion is that the ADB1 housing complex community is still not satisfied with waste management, and it is also urgently needed support from various parties, both government and institutions related to waste management.